2005
DOI: 10.1002/ejoc.200400453
|View full text |Cite|
|
Sign up to set email alerts
|

Synthetic Approaches to Sterically Hindered N‐Arylimidazoles through Copper‐Catalyzed Coupling Reactions

Abstract: Optimization studies allowed the efficient synthesis of a simple structural motif based on meta‐bis(1‐imidazolyl)benzenes 1 through copper‐catalyzed coupling of 1,3‐diiodobenzene and imidazole under mild reaction conditions. This protocol was then used to prepare a representative sterically hindered N‐arylimidazole 2a, the most common structural motif among N‐heterocyclic carbenes (NHC). Having optimized the main variables governing CuI‐catalyzed imidazole N‐arylation, the first Ullmann‐type synthesis of N‐mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The addition of a small amount of water was found beneficial in some amidation reactions [529]. Palladium catalyzed the intermolecular N-arylation or N-alkenylation of primary and secondary amines [530,531], polyamines [532], imidazoles [533], benzophenone hydrazine [376], N,N-dialkylhydrazines [534], sulfoximines [535,536] in a synthesis of erogorgiaene [350], sulfamides [537], pyrroles and indoles [538], aziridines [539], zinc trimethylsilylamide, as an ammonia equivalent [540], of 15 N-labelled benzamide [541], ureas [542] and linear polyamines [543] using aryl halides or alkenyl triflates. This type of reaction using a 3,5-dibromopyridine and aza-substituted 1,n-diamines was used to prepare polyazamacrocycles [544].…”
Section: Carbon-oxygen -Nitrogen and -Sulfur Bond-forming Reactionsmentioning
confidence: 99%
“…The addition of a small amount of water was found beneficial in some amidation reactions [529]. Palladium catalyzed the intermolecular N-arylation or N-alkenylation of primary and secondary amines [530,531], polyamines [532], imidazoles [533], benzophenone hydrazine [376], N,N-dialkylhydrazines [534], sulfoximines [535,536] in a synthesis of erogorgiaene [350], sulfamides [537], pyrroles and indoles [538], aziridines [539], zinc trimethylsilylamide, as an ammonia equivalent [540], of 15 N-labelled benzamide [541], ureas [542] and linear polyamines [543] using aryl halides or alkenyl triflates. This type of reaction using a 3,5-dibromopyridine and aza-substituted 1,n-diamines was used to prepare polyazamacrocycles [544].…”
Section: Carbon-oxygen -Nitrogen and -Sulfur Bond-forming Reactionsmentioning
confidence: 99%
“…Aerobic conditions were required to ensure conversion to the desired products, as O 2 plays a crucial role in regenerating the active catalyst within the catalytic cycle. [73] Buchwald et al also describe the copper-diamine-complex-catalyzed Narylation of imidazoles and some other π-excessive nitrogen heterocycles (pyrroles, pyrazoles, indazoles, triazoles). [68][69][70][71] Scheme 29. In the course of the development of new bis(carbene) ligands for cross-coupling reactions, double copper-catalyzed C-N bond formation on 1,3-dibromobenzene (85) provided 1,1Ј-(1,3-phenylene)-bis(1H-imidazole) (86) in 77 % yield (Scheme 30).…”
Section: C-n Bond Formationmentioning
confidence: 99%
“…[72] Recently, sterically demanding aryl iodides were applied in C-N bond formations with imidazole under mild reaction conditions. [73] Buchwald et al also describe the copper-diamine-complex-catalyzed Narylation of imidazoles and some other π-excessive nitrogen heterocycles (pyrroles, pyrazoles, indazoles, triazoles). [74] Scheme 30.…”
Section: C-n Bond Formationmentioning
confidence: 99%
“…Moreover, simple diamine ligands for CuI have also been used for the arylation of indoles, [6] pyrroles, pyrazoles, indazoles, imidazoles, and triazoles. [7] Recent developments reported by Chan and Lam [8] have demonstrated that arylboronic acids can be effective as arylating agents when stoichiometric quantities of Cu(OAc) 2 are used; these experimental conditions have been applied to the arylation of azoles, [9] pyrrole and methyl indole-2-carboxylate derivatives, [10] sterically hindered imidazoles, [11] and electron-deficient pyrroles. [12] More recently, heteroarenes have been arylated with catalytic Cu(OAc) 2 in the presence of stoichiometric amounts of mild oxidizing agents, [13] while Collman [14] has reported the arylation of In contrast, there are fewer examples of C-N bond formation as a method for N-vinylation through the use of boronic acids or esters.…”
Section: Introductionmentioning
confidence: 99%